2018
DOI: 10.1002/14651858.cd008449.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Mirror therapy for improving motor function after stroke

Abstract: Analysis 5.1. Comparison 5 Sensitivity analysis by trial methodology, Outcome 1 Motor function at the end of intervention....... Analysis 5.2. Comparison 5 Sensitivity analysis by trial methodology, Outcome 2 Motor impairment at the end of intervention.... Analysis 6.1. Comparison 6 Post hoc sensitivity analysis removing studies that only included participants with CRPS a er stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
194
0
34

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 270 publications
(264 citation statements)
references
References 131 publications
4
194
0
34
Order By: Relevance
“…Weakened parietal-to-M1 interactions (Grefkes and Fink, 2011, Takeuchi et al, 2012) have been previously identified in stroke, and restoring functional interactions among this network has been positively correlated with good recovery (Carter et al, 2010, van Meer et al, 2010, Wang et al, 2010, Grefkes and Fink, 2011, Rehme et al, 2011, Rehme et al, 2012, van Meer et al, 2012, De Vico Fallani et al, 2016). Mirror feedback, therefore, may be a useful clinical tool, as it has been shown to improve some outcomes in moderately to severely impaired patients (Thieme et al, 2012, Thieme et al, 2013, Pollock et al, 2014), and to activate specific networks that may favor recovery, particularly in patients who cannot otherwise engage their paretic hand in exercise. It remains unknown if similar networks could be activated in acutely impaired stroke patients; this is a focus of ongoing investigations in our lab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weakened parietal-to-M1 interactions (Grefkes and Fink, 2011, Takeuchi et al, 2012) have been previously identified in stroke, and restoring functional interactions among this network has been positively correlated with good recovery (Carter et al, 2010, van Meer et al, 2010, Wang et al, 2010, Grefkes and Fink, 2011, Rehme et al, 2011, Rehme et al, 2012, van Meer et al, 2012, De Vico Fallani et al, 2016). Mirror feedback, therefore, may be a useful clinical tool, as it has been shown to improve some outcomes in moderately to severely impaired patients (Thieme et al, 2012, Thieme et al, 2013, Pollock et al, 2014), and to activate specific networks that may favor recovery, particularly in patients who cannot otherwise engage their paretic hand in exercise. It remains unknown if similar networks could be activated in acutely impaired stroke patients; this is a focus of ongoing investigations in our lab.…”
Section: Discussionmentioning
confidence: 99%
“…These data, therefore, provide a neural basis for virtual mirror feedback, by showing that mirror feedback can activate ipsilesional motor-related hubs that are important for the recovery process. The findings about the neural underpinnings of mirror feedback are encouraging particularly in light of recent clinical studies showing that MVF may show promise in restoring function after stroke (Yavuzer et al, 2008, Dohle et al, 2009, Thieme et al, 2012, Thieme et al, 2013). The goal of this project is to fill this gap by identifying the neural network and mechanisms by which the ipsilesional motor cortex is facilitated by MVF.…”
Section: Introductionmentioning
confidence: 87%
“…This experiment is " based on Mirror therapy based non-invasive treatment of chronic stroke patients [56]. subject's forearm in the intended direction {t right } or {t lef t } (repeated every 2 s).…”
Section: !'mentioning
confidence: 99%
“…This nding $ emerged as the central element in rehabilitation of stroke patients to regain their motor functions. movement therapy [24] and mirror-based therapies [56]. They can be divided in three categories such as human assisted therapy [15], robotics ' assisted therapy [31] and the emerging Brain-Computer Interface (BCI) assisted robot therapies [34] [ 43][51].…”
mentioning
confidence: 99%
“…It is proposed that MT acts to restore the correspondence between motor output (commands sent to the affected limb) and sensory input (visual feedback of the affected limb moving as commanded) [11], and thus enhances recovery of motor control in the affected limb. Motor outcomes associated with upper limb MT include motor recovery as measured by the Brunnstrom stages and Fugl-Meyer [15, 16, 17], and improved speed and accuracy of movement [10] (see Thieme et al [18], Rothgangel et al [19] and Ezendam et al [20] for reviews).…”
Section: Introductionmentioning
confidence: 99%